ANALISIS KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muhammad Fikri Arrazi (2021)
This study aims to determine the influence of profitability, liquidity, solvency and activity on the value of the company by using a sample of cement companies listed on the Indonesia Stock Exchange from 2014 to 2019. The samples used were five companies and were collected using saturated sample techniques. This study used Microsoft Excel 2019 to analyze its data and E-Views 11 by using panel data regression analysis method. The significance rate of this study is 5%. The results of this study showed that profitability (ROA) and solvency (DAR) have a positive effect on the company's value (PBV), while activity (TAT) negatively affects the value of the company (PBV), and liquidity negatively affects the value of the company Has no effect (PBV).